Nutrients’ critical level propositions and sufficiency ranges aimed at high apple yield under subtropical climate - Trapp, Talita (2025)
Apple yield can be maximized through balanced nutritional management of orchards. This can be achieved by defining nutritional standards and nutrient reference values through multivariate database analysis. The objectives of the study were: i) to set and compare apple trees’ nutritional standards based on the Diagnosis and Recommendation Integrated System (DRIS) and on the Composition Nutritional Diagnosis (CND) and ii) to generate nutrients’ critical levels (CL) and sufficiency ranges (SR) in relation to the productivity of apple trees. The study was carried out in commercial Gala and Fuji cultivar orchards in Fraiburgo, Lebon Régis, Santa Cecília, and Monte Carlo municipalities - Santa Catarina State, Brazil. A database comprising information on fruit yield and leaf nutrient contents, from 10,179 observations performed from 2006 to 2021 was used in the study. According to the results, there is low association between mean nutrient balance index (NBIm) and nutritional imbalance index (CND-r²), and yield. DRIS and CND methods were effective in diagnosing apple trees’ nutritional status. Apple trees’ greatest nutritional requirements comprise the following macronutrients: nitrogen (N), potassium (K) and calcium (Ca), and the following micronutrients: manganese (Mn), iron (Fe) and zinc (Zn), all of them determined through the CND method. CL and SR established through the DRIS and CND methods were alike, but the best-adjusted SRs were found through CND: 22.1 – 26.4; 1.4 – 2.1; 11.5 – 15.8; 11.0 – 15.2; 2.9 – 4.0 g kg−1 and 70.2 – 116.7; 208.2 – 552.7; 5.8 – 8.6; 99.3 – 182.9; 31.4 – 41.9 mg kg−1 for N, P, K, Ca, Mg, Fe, Mn, Cu, Zn and B, respectively, for the cv. Gala; and 24.3 – 28.5; 1.6 – 2.2; 10.7 – 15.0; 12.0 – 16.01; 2.7 – 3.8 g kg−1 and 75.9 – 125.6; 107.3 – 364.1; 6.1 – 9.1; 43.4 – 124.4; 32.8 – 44.3 mg kg−1 for N, P, K, Ca, Mg, Fe, Mn, Cu, Zn and B, respectively, for the cv. Fuji. The use of the CL and SR standards established here will allow the rational use of fertilizers, but also the adequate nutritional balance of the orchards to achieve the greatest yield efficiency.